2018
DOI: 10.1136/neurintsurg-2018-013845
|View full text |Cite
|
Sign up to set email alerts
|

Unique percutaneous direct puncture technique for occlusion of a hypoglossal canal dural arteriovenous fistula

Abstract: With guidance and imaging provided by CBCT and syngo iGuide navigational software, an otherwise untreatable DAVF was successfully embolized and obliterated by an aggressive unique percutaneous trans-cranial needle puncture of the dominant outflow vein in the hypoglossal canal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…At present, the main treatment methods are TAE, TVE, surgery, and radiotherapy. TAE carries a significant risk of inferior cranial nerve palsy and embolic stroke because the neurovessels of the inferior cranial nerves (IX-XII) are derived from the neuromeningeal trunk of the ascending pharyngeal artery (6)(7)(8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, the main treatment methods are TAE, TVE, surgery, and radiotherapy. TAE carries a significant risk of inferior cranial nerve palsy and embolic stroke because the neurovessels of the inferior cranial nerves (IX-XII) are derived from the neuromeningeal trunk of the ascending pharyngeal artery (6)(7)(8).…”
Section: Discussionmentioning
confidence: 99%
“…Dahl et al reported a case of successful treatment of HCDAVF by intravenous coil embolization through the deep cervical vein as an alternative access to the ACC after the failure of the trans-IJV approach ( 11 ). Diaz et al reported a case of HCDAVF in which, after embolization and surgical failure, the anterior condylar vein was punctured percutaneously at the hypoglossal foramina and occluded with onyx after placing two anchor coils ( 6 ). Júnior et al reported a case of HCDAVF in which the ACC was occluded by direct puncture of the cavernous sinus after transvenous access was unavailable ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given the proximity of the venous pouch to the posterior wall of the sphenoid sinus, we determined that a transsphenoidal approach would enable us to directly access the venous pouch for Onyx embolization. Direct puncture and embolization of the venous pouch has been successfully described for dAVFs of the skull base such as the hypoglossal canal, 14 but not via an endoscopic endonasal transsphenoidal approach. Our ability to perform this ap- proach was dependent on a full understanding of the venous outflow of the fistula and the availability of a hybrid operating room.…”
Section: Discussionmentioning
confidence: 99%
“…4 Transarterial embolization carries a significant risk of cranial nerve injury and potential non-target embolization. 3 , 4 Although direct puncture of the hypoglossal canal may be feasible, 12 alternative venous routes should be considered and exhausted before performing more aggressive procedures.…”
Section: Discussionmentioning
confidence: 99%